Proline addition increases the efficiency of l‐lysine production by Corynebacterium glutamicum. Issue 4 (4th July 2013) - van, Jan; Noack, Stephan; Bott, Michael; Eggeling, Lothar
<x xml:space="preserve">Abstract</x> The wild type of Corynebacterium glutamicum does not excrete l‐lysine, but mutants are developed to use C. glutamicum for the large‐scale production of this amino acid. l‐lysine is derived from oxaloacetate and pyruvate. A reduced entry of these precursors into the citric acid cycle triggers l‐lysine synthesis, but there is simultaneously an unfavorable reduction in growth rate. Here, we further investigated strains with reduced citrate synthase activity and observed that proline supplementation partly reversed the growth rate reduction, and simultaneously increased l‐lysine accumulation by 10%. The combined effect of faster growth and higher l‐lysine formation lead to an increase in l‐lysine productivity of about 14%. Small scale bioreactor cultivations showed an increase of the glucose uptake rate from 3.96 to 5.12 mmol gCDW−1 h−1 as the effect of proline addition. Deletion of the proline‐utilization gene putA demonstrated that proline did not serve to refill the citric acid cycle. The combined data show that proline addition has a favorable effect on l‐lysine formation and sugar uptake, which indicates that engineering sugar uptake is a future option for increased product formation.